Licensing of Pesticide Dealers in Florida - Frederick M. Fishel (EDIS, 2005)
This document explains who needs a pesticide dealer license in Florida, how to obtain the license and the records required to be kept by pesticide dealers.  This document is PI-49, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 2005.